2019
DOI: 10.3390/rs11212486
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Improvement of Sea Surface Microwave Emission Models for Salinity Retrieval in the East China Sea

Abstract: Accurate prediction of sea surface emission is the key for sea surface salinity retrieval from satellite microwave radiometer. In order to retrieve salinity from satellite observation, several sea surface microwave emission models have been developed based on theoretical or empirical methods and validated by in-situ measurements in different regions. However, their performances are still unclear in the Chinese coastal waters. In this study, based on two cruises measurements in the East China Sea (ECS), includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Studies have reported satisfactory performance using microwave sensors for the estimation of salinity/TDS and TSS in ocean waters. Examples include the study by [218] where ship-borne microwave radiometer data were used to develop improved sea surface microwave emission models or algorithms for the retrieval of sea surface salinity. The authors found root mean square error (RMSE) or differences between the in situ and retrieved sea surface salinity of around 0.4 Practical Salinity Units (PSU) which indicates good model performance.…”
Section: Summary Of Studies On Tds and Tss Estimation With Rs Applica...mentioning
confidence: 99%
“…Studies have reported satisfactory performance using microwave sensors for the estimation of salinity/TDS and TSS in ocean waters. Examples include the study by [218] where ship-borne microwave radiometer data were used to develop improved sea surface microwave emission models or algorithms for the retrieval of sea surface salinity. The authors found root mean square error (RMSE) or differences between the in situ and retrieved sea surface salinity of around 0.4 Practical Salinity Units (PSU) which indicates good model performance.…”
Section: Summary Of Studies On Tds and Tss Estimation With Rs Applica...mentioning
confidence: 99%